Imprinted Gene Expression and Function of the Dopa Decarboxylase Gene in the Developing Heart - Prickett, Adam R.; Montibus, Bertille; Barkas, Nikolaos; Amante, Samuele M.; Franco, Maurício M.; Cowley, Michael; Puszyk, William; Shannon, Matthew F.; Irving, Melita D.; Madon-Simon, Marta; Ward, Andrew; Schulz, Reiner; et al. (Frontiers in Cell and Developmental Biology, 2021)
Dopa decarboxylase (DDC) synthesises serotonin in the developing mouse heart where it is encoded by Ddc_exon1a, a tissue-specific paternally expressed imprinted gene. Ddc_exon1a shares an imprinting control region (ICR) with the imprinted, maternally expressed (outside of the central nervous system) Grb10 gene on mouse chromosome 11, but little else is known about the tissue-specific imprinted expression of Ddc_exon1a. Fluorescent immunostaining localises DDC to the developing myocardium in the pre-natal mouse heart, in a region susceptible to abnormal development and implicated in congenital heart defects in human. Ddc_exon1a and Grb10 are not co-expressed in heart nor in brain where Grb10 is also paternally expressed, despite sharing an ICR, indicating they are mechanistically linked by their shared ICR but not by Grb10 gene expression. Evidence from a Ddc_exon1a gene knockout mouse model suggests that it mediates the growth of the developing myocardium and a thinning of the myocardium is observed in a small number of mutant mice examined, with changes in gene expression detected by microarray analysis. Comparative studies in the human developing heart reveal a paternal expression bias with polymorphic imprinting patterns between individual human hearts at DDC_EXON1a, a finding consistent with other imprinted genes in human.